Impact of COVID-19 on Student’s Emotional and Financial Aspects in the Higher Learning Institutions - Haji Wahab, Muhammad Zarunnaim; Othman, Kamarudin (SEISENSE Journal of Management, 2021)
Purpose- This paper aims to determine the impact of the COVID-19 pandemic on the student’s financial and emotional aspect at one of Malaysia's higher learning institutions (HLI). Design/Methodology- The data collected from the online questionnaires involved 397 students and were analyzed using SPSS. Findings- The findings showed a significant positive association between all variables where the strength range was from r=.556 to r=.565. The highest correlation is the financial aspect (r-value .565) and is followed by the emotional aspect (.556). Next, the results also revealed that both variables were significantly influenced where the R² value was 47.1% while other factors explained the additional 53% of the element. Practical Implications- There are some significant implications identified in this study. First, this study's findings directly impacted the COVID-19 pandemic, especially in terms of financial support and the emotional aspect. Second, the result indicated that the university should also consider other internal and external aspects rather than focus only on improving the learning process. Third, this study would enrich the current body of knowledge about the impact of COVID-19.